(5E, 7E)-4, 5, 6 Trihydroxy-3-(hydroxymethyl)tetrahydro-2H-pyran-2-ylheptadeca-5, 7-dienoate from Euclea crispa (L.) Inhibits Ovarian Cancer Cell Growth by Controlling Apoptotic and Metastatic Signaling Mechanisms. (29th January 2022) - Palanisamy, Chella Perumal; Cui, Bo; Zhang, Hongxia; Jayaraman, Selvaraj; Rajagopal, Ponnulakshmi; Veeraraghavan, Vishnu Priya
Abstract : Bioactive compound (5E, 7E)-4, 5, 6 trihydroxy-3-(hydroxymethyl)tetrahydro-2H-pyran-2-ylheptadeca-5, 7-dienoate (compound 2) was isolated from Euclea crispa ( E. crispa ) by the chromatographic methods. Further, the compound was confirmed by spectroscopic techniques such as ultraviolet-visible (UV/Vis) spectrometer, Fourier transform infrared (FTIR) spectrometer, and 1 H and 13 C nuclear magnetic resonance (NMR). Compound 2 exhibited a significant antioxidant activity with IC50 values. It restrained the auxesis of HO-8910 cells in a shot-dependent mode. CXCR4, HER2, and Akt proteins involved in cell proliferation and metastasis were found to be significantly reduced (p < 0.05 ). The protein that is responsible for the death of cells (Bcl-2 and Bcl-xL) was reduced (p < 0.05 ), while the protein expression of p53 and caspase-9 was increased (p < 0.05 ) in compound 2-treated HO-8910 cells. The results of molecular docking analysis showed the binding affinity with CXCR4 and HER2. Thus, compound 2 can serve as a promising chemotherapeutic agent for the intervention of ovarian cancer. The findings of this study conclude that compound 2 from E. crispa might work as a potential antioxidative and chemotherapeutic agent. The in vivo studies and attempts will pave way for this compound to be an effective drug hereafter.